MORPHOGENESIS OF THE ZERO-STAGE OSTEONECROSIS FORMATION OF THE LOWER JAW BASED ON THE USE OF AMINOBISPHOSPHONATES - Pikalyuk, V.S.; Mostovoy, S.O.; Peshkov, M.V.; Tkach, G.F.; Shevchuk, T.Ya.; Aponchuk, L.S.; Usova, O.V. (World of Medicine and Biology, 2022)
The dynamics of morphostructural changes in the mandibular bones of laboratory white rats after a 3-month exposure to pamidronic acid at the dose of 63 mg/kg was studied. Light microscopy methods were used, including qualitative and quantitative characteristics in assessing the structural state of the bone through the parameters that characterize the histoarchitectonics of the lower jaw using indices and their abbreviations proposed by the committee on histomorphometric nomenclature of American Society for Bone and Mineral Research. Three new functional indices for assessing physiological processes in bones were studied. It was established that administration of pamidronic acid to laboratory white rats for 3 months leads to myelofibrosis and focal osteosclerosis with osteodystrophic changes, similar to the processes that develop in ossifying osteitis.
Keywords: aminobisphosphonate; osteonecrosis; osteocytic osteolysis; lower jaw